Human resource management and coordination for innovation activities: gleanings from Malaysian cases. Issue 2 (4th May 2017) - Mohan, Avvari V.
ABSTRACT: This study explores human resource management (HRM) and coordination for research and development (R&D) or innovation-related activities in companies operating in Malaysia. The case studies conducted show that internal mechanisms like recruitment and training can be seen as hygiene factors in all three organisations. Reward systems were not discussed as critical in all three cases. In order for the organisations to up their level of technological or innovation capability, external mechanisms for human resource development can be seen as critical. This varied in terms of developing links with a foreign university for training and also joint projects in the case of large conglomerates, the foreign subsidiary sending personnel to the R&D centre of the headquarters and links with the government research institute, which was critical. In all the cases, the role of the top management in supporting the R&D (formal or informal) function was crucial for innovation capabilities.